Respuesta :
f(x) = 8x³ - 22x² - 4
g(x) = 4x - 3
[tex](f \div g)(x) = \frac{8x^{3} - 22x^{2} - 4}{4x - 3}[/tex]
[tex](f \div g)(x) = \frac{2(4x^{3}) - 2(11x^{2}) - 2(2)}{4x - 3}[/tex]
[tex](f \div g)(x) = \frac{2(4x^{3} - 11x^{2} - 2)}{4x - 3}[/tex]
g(x) = 4x - 3
[tex](f \div g)(x) = \frac{8x^{3} - 22x^{2} - 4}{4x - 3}[/tex]
[tex](f \div g)(x) = \frac{2(4x^{3}) - 2(11x^{2}) - 2(2)}{4x - 3}[/tex]
[tex](f \div g)(x) = \frac{2(4x^{3} - 11x^{2} - 2)}{4x - 3}[/tex]
Answer:
[tex]\frac{f(x)}{g(x)}=\frac{2(4x^3-11x^2-2)}{4x-3}[/tex]
Step-by-step explanation:
The given functions are.....
[tex]f(x)= 8x^3-22x^2-4\\ \\ g(x)=4x-3[/tex]
Using the above functions, we will get......
[tex]\frac{f(x)}{g(x)}\\ \\ =\frac{8x^3-22x^2-4}{4x-3}\\ \\ =\frac{2(\frac{8x^3}{2}-\frac{22x^2}{2}-\frac{4}{2})}{4x-3}\\ \\ =\frac{2(4x^3-11x^2-2)}{4x-3}[/tex]